Jasmonic and Salicylic Acids Enhance Biomass, Total Phenolic Content, and Antioxidant Activity of Adventitious Roots of Acmella radicans (Jacq.) R.K. Jansen Cultured in Shake Flasks - Antonio Bernabé-Antonio; Clarisa Castro-Rubio; Raúl Rodríguez-Anda; José Antonio Silva-Guzmán; Ricardo Manríquez-González; Israel Hurtado-Díaz; Mariana Sánchez-Ramos; Gabriela Hinojosa-Ventura; Antonio Romero-Estrada (Biomolecules, 2023)
Acmella radicans (Asteraceae) is a plant native to America. Despite it having medicinal attributes, studies on its phytochemical properties are scarce, and biotechnological studies do not exist for this species. In this study, we established an adventitious root culture from A. radicans internodal segments in shake flasks with indole-3-butyric acid (IBA), and then elicited it with jasmonic acid (JA) and salicylic acid (SA). The total phenolic content and antioxidant activity were evaluated, and a comparison was made using in vitro plantlets and wild plants. Internodal segments with 0.1 mg/L IBA showed 100% root induction and exhibited better growth after transfer to shake flasks with MS liquid culture medium. JA had a significant effect on biomass increase compared to unelicited roots, mainly with 50 µM JA (28%), while SA did not show significant results. Root elicited with 100 µM (SA and JA) showed a 0.34- and 3.9-fold increase, respectively, in total phenolic content (TPC) compared to the control. The antioxidant activity was also significant, and a lower half-maximal inhibitory concentration (IC50) was observed as the AJ concentration increased. Roots elicited with AJ (100 µM) exhibited high antioxidant activity with DPPH (IC50 = 9.4 µg/mL) and ABTS (IC50 = 3.3 µg/mL) assays; these values were close to those for vitamin C (IC50 = 2.0 µg/mL). The TPC and antioxidant activity of in vitro plants and root cultured in shake flasks showed the lowest values in most cases; even the root cultures without elicitation were better than those of a wild plant. In this study, we demonstrated that A. radicans root culture is capable of producing secondary metabolites, while its production and antioxidant activity can be enhanced using jasmonic acid.